2010
DOI: 10.1002/pmj.20194
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Collaboration in Multipartner Projects

Abstract: In many project-based industries, there has recently been an increased tendency for collaboration and cocreation of value with the customers. However, many existing studies report inherent challenges and complexities related to multipartner collaboration. This article presents a conceptual framework that explains the focal collaboration-related elements and their interdependencies in multipartner projects. The elements in the framework and relations between them are derived from the existing empirical studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
128
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(156 citation statements)
references
References 127 publications
10
128
0
6
Order By: Relevance
“…En la década pasada se hicieron investigaciones para aplicar el modelo en conjunto de universidades del Reino Unido, donde enfatizaron la metodología para la autoevaluación, proporcionando información relevante que permite deducir que se favorece la orientación hacía el estudiante por parte de las instituciones que lo aplican. Otros autores, dan cuenta de diferentes elementos que apoyan la gestión de calidad y que también forman parte del EFQM, como elementos centrales a ser considerados [4][5][6][7][8].…”
Section: Antecedentesunclassified
See 2 more Smart Citations
“…En la década pasada se hicieron investigaciones para aplicar el modelo en conjunto de universidades del Reino Unido, donde enfatizaron la metodología para la autoevaluación, proporcionando información relevante que permite deducir que se favorece la orientación hacía el estudiante por parte de las instituciones que lo aplican. Otros autores, dan cuenta de diferentes elementos que apoyan la gestión de calidad y que también forman parte del EFQM, como elementos centrales a ser considerados [4][5][6][7][8].…”
Section: Antecedentesunclassified
“…Entre los elementos que se destacan y que el modelo EFQM considera como relevante para ser efectivo en su aplicación, es que se requiere que se integren y alineen diferentes componentes de la organización, como lo son el planeamiento, el involucramiento del personal por medio de la conformación de equipos para abordar la autoevaluación e introducir cambios, y destaca la "performance" gerencial como un elemento transversal para que los cambios ocurran [8].…”
Section: Antecedentesunclassified
See 1 more Smart Citation
“…It is commonly stated that promotional mechanisms are not obvious, there are many benefit conflicts and little trust among participant groups, so maybe altruistic help and sharing behavior disappeared. While some empirical studies have shown that altruism and reciprocal preference appear to be strongly related to cooperation in CMP, as the overall project success is decision-based, participants still like to help each other without promotion as motivation (Aronson et al, 2013;Han, Zhou & Li, 2014;Dai & Yu, 2003); knowledge and resources sharing prevailed and were critical cooperation factors (Braun et al, 2013;Hanisch & Wald, 2014;Dietrich, Eskerod, Dalcher & Sandhawalia, 2010). So help behavior may be conceptualized as "Cooperation Behavior (CoB)" which means "common cooperative efforts that CMP participants conduct together to achieve project and individual goals".…”
Section: Cooperation Behavior (Cob)mentioning
confidence: 99%
“…This strengthened the nature of their collaboration and encouraged open sharing of information and knowledge (DIETRICH et al, 2010;WHEATLEY, 2003, REEVES, 2004DARLING;ROSS, 2000).…”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%